Education Research: Multiple sclerosis and neuroimmunology fellowship training status in the United States. (17th March 2020) - Obeidat, Ahmed Z.; Jassam, Yasir N.; Hua, Le H.; Cutter, Gary; Ford, Corey C.; Halper, June; Lisak, Robert P.; Sicotte, Nancy L.; Longbrake, Erin E.
Abstract : Objective: To investigate the current status of postgraduate training in neuroimmunology and multiple sclerosis (NI/MS) in the United States. Methods: We developed a questionnaire to collect information on fellowship training focus, duration of training, number of fellows, funding application process, rotations, visa sponsorship, and an open-ended question about challenges facing training in NI/MS. We identified target programs and sent the questionnaires electronically to fellowship program directors. Results: We identified and sent the questionnaire to 69 NI/MS fellowship programs. We successfully obtained data from 64 programs. Most programs were small, matriculating 1–2 fellows per year, and incorporated both NI and MS training into the curriculum. Most programs were flexible in their duration, typically lasting 1–2 years, and offered opportunities for research during training. Only 56% reported the ability to sponsor nonimmigrant visas. Most institutions reported having some internal funding, although the availability of these funds varied from year to year. Several program directors identified funding availability and the current absence of national subspecialty certification as major challenges facing NI/MS training. Conclusion: Our study is the first to describe the current status of NI/MS training in the United States. We found many similarities across programs. We anticipate that these data will serve as a first step towards developing a standard NI/MS curriculum and help identify areas where shared resources could enhance trainee education despite differences in training environments. We identified funding availability, certification status, and nonimmigrant visa sponsorship as potential barriers to future growth in the field.